2016
DOI: 10.1007/s13346-016-0326-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEG and water-soluble chitosan coating on moxifloxacin-loaded PLGA long-circulating nanoparticles

Abstract: Moxifloxacin (MOX) is a Mycobacterium tuberculosis DNA gyrase inhibitor. Due to its intense hydrophilicity, MOX is cleared from the body within 24 h and required for repetitive doses which may then result in hepatotoxicity and acquisition of MOX resistant-TB, related with its use. To overcome the aforementioned limitations, the current study aimed to develop PLGA nanoparticles (PLGA NPs), to act as an efficient carrier for controlled delivery of MOX. To achieve a substantial extension in blood circulation, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…This is thought to be related to the low clearance and the length of the half‐life of amoxicillin‐loaded nps. In some studies, it has been reported that surfactants and polymers incorporated into the formulation cause prolonging half‐life of drugs by reducing reticuloendothelial system‐mediated clearance and opsonization of nanoparticles (Chaudhari et al., ; Mustafa, Devi, & Pai, ; Parveen & Sahoo, ). As a result of the evaluation based on the comparative plasma drug concentration–time curves, it was found that amoxicillin nps slowly releases in the gastrointestinal tract and provides steady‐state drug concentration for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be related to the low clearance and the length of the half‐life of amoxicillin‐loaded nps. In some studies, it has been reported that surfactants and polymers incorporated into the formulation cause prolonging half‐life of drugs by reducing reticuloendothelial system‐mediated clearance and opsonization of nanoparticles (Chaudhari et al., ; Mustafa, Devi, & Pai, ; Parveen & Sahoo, ). As a result of the evaluation based on the comparative plasma drug concentration–time curves, it was found that amoxicillin nps slowly releases in the gastrointestinal tract and provides steady‐state drug concentration for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…PLGA nanoparticles, as a safe drug-loading system, can effectively slow the drug release and protect drugs from gastrointestinal degradation (Lozoya-Agullo et al, 2017; Mustafa et al, 2017). Then coating the lipid membrane on the particles can further protect the drugs from GI and improve the contact between the nanoparticles and the small intestinal epithelial cells, which may achieve the goal of prolonging the circulation in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Another polymer frequently mixed with PLGA is polyethylene glycol (PEG) ( Zhang et al, 2014 ). PEG is a nonionic biocompatible polymer coated onto the surfaces of nanoparticles that prevents recognition and destruction of these carriers by the mononuclear phagocyte system (MPS), thereby increasing the plasma half-lives of the nanoparticles ( Mustafa et al, 2017 ). Furthermore, PEGylation of nanoparticles improves their stability by reducing intermolecular aggregation and the accessibility of the target site ( Gref et al, 2000 ).…”
Section: Nanomedicinementioning
confidence: 99%